Theoretical Study On Neutral Complexes M\(^±\) (H\(_2\)O) \(_n\) - Fatma Benyettou (Theoretical Study On Neutral Complexes M\(^±\) (H\(_2\)O) \(_n\), 2025)
The evolution of quantum theory, molecular dynamics, the performance of optimization algorithms and the availability of high-performance computer power have made it possible to simulate the description of the stability of ions in solution and at the level of complexes. Our theoretical study at different ab initio levels is based on optimizing and simulating the different systems studied. This study has provided us with information on the structure, the number of hydration coordinates and the nature of the bonds of the neutral complexes and that the results found give an excellent agreement with the experimental values.